2017
DOI: 10.5114/hivar.2017.66859
|View full text |Cite
|
Sign up to set email alerts
|

Long-term comparative and prospective cohort study of renal function in patients with HIV infection treated with tenofovir disoproxil fumarate

Abstract: Introduction: Evidence regarding long-term evolution of renal function in patients with human immunodeficiency virus (HIV) infection treated with tenofovir disoproxil fumarate (TDF) is scarce and often retrospective.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 26 publications
(47 reference statements)
0
1
0
Order By: Relevance
“…Calle et al described a significant decline in renal function in a long term observational prospective cohort study studied over 7.5 years and attributed this change to the use of Tenofovir. 18 Kumarasamy et al described a similar relationship with Tenofovir use. 19 Mulenga et al also found in their adjusted analysis that patients receiving TDF were more likely to experience an episode of moderate or severe renal dysfunction than those receiving other regimens during the first year of ART, although the incidence of such episodes was low.…”
Section: Discussionmentioning
confidence: 90%
“…Calle et al described a significant decline in renal function in a long term observational prospective cohort study studied over 7.5 years and attributed this change to the use of Tenofovir. 18 Kumarasamy et al described a similar relationship with Tenofovir use. 19 Mulenga et al also found in their adjusted analysis that patients receiving TDF were more likely to experience an episode of moderate or severe renal dysfunction than those receiving other regimens during the first year of ART, although the incidence of such episodes was low.…”
Section: Discussionmentioning
confidence: 90%